"Is There No Alternative?": An Overdeterminist Marxian Class Analysis of International Political Economy. Issue 4 (2nd October 2019) - Düzenli, Faruk Eray
Abstract : David F. Ruccio's Development and Globalization is a collection of remarkable interventions, elegantly articulated, into debates over socialist planning, Third World development, and capitalist globalization from a postmodernist Marxian class-analytical perspective. Ruccio's analyses are both theoretical and empirical. They also provide superb examples of how the focus in the field of international political economy has changed over time, from planning to development and eventually to globalization. Yet this does not mean that these essays are a thing of the past; they not only provide the questions and the methodology with which economists should do research but also remind us why it is important for us to think, in new ways, about international political economy.